Evaluación de ansiedad preoperatoria en pacientes sometidos a cirugía electiva en el Hospital General Regional N° 1 - Morano Santos, Laura Montserrat (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The anxiety that the patient presents before the need to face an anesthetic-surgical act, manifests as psychological and physical discomfort. The reported frequency ranges from 30 to 50%. We consider that there is a high percentage of patients at risk. Objective: To identify the frequency of preoperative anxiety in patients undergoing elective surgery at Hospital General Regional No. 1. Material and Methods: Observational, descriptive, prospective study carried out on 200 patients undergoing elective surgery at Hospital General Regional No. 1. Patients older than 18 years, any sex, ASA I-III were included. Orointubated patients or patients with neurological deficit were not included. The objective of the study was explained, requesting the signature of the consent. Age, sex, ASA, comorbidities were recorded, evaluating preoperative anxiety with the Hamilton scale and the APAIS scale. Results: APAIS detected a prevalence of 57% (113 patients), the Hamilton scale detected 13% (26 patients) with clinical manifestations of anxiety. The average age was 46.4 years SD 12.18; 58% female and 42% male. Physical status was 6% ASA I, 61% ASA II, and 33% ASA III. The main comorbidities were: 20% hypertensive disease and 11% diabetes mellitus. The Surgical Services with the highest frequency of anxiety were: 35% traumatology and orthopedics, 16% gynecology and obstetrics, 13% general surgery. Conclusions: In Hospital General Regional No. 1, the prevalence of preoperative anxiety is high. The APAIS and Hamilton scales should be included in the preanesthetic visit in order to identify patients at risk.

La ansiedad que presenta el paciente ante la necesidad de enfrentar un acto anestésico-quirúrgico, se manifiesta como malestar psíquico y físico. La frecuencia reportada va de 30 a 50%. Consideramos que existe un alto porcentaje de pacientes en riesgo. Objetivo: Identificar la frecuencia de ansiedad preoperatoria en paciente sometidos a cirugía electiva en el Hospital General Regional Núm. 1. Material y Métodos: Estudio observacional, descriptivo, prospectivo realizado en 200 pacientes sometidos a cirugía electiva en el Hospital General Regional Núm. 1. Se incluyeron pacientes mayores a 18 años, cualquier sexo, ASA I-III. No se incluyeron pacientes orointubados o con déficit neurológico. Se explicó el objetivo del estudio solicitando la firma del consentimiento. Se registró edad, sexo, ASA, comorbilidades, evaluando ansiedad preoperatoria con la escala Hamilton y la escala APAIS. Resultados: APAIS detectó una prevalencia de 57% (113 pacientes), la escala Hamilton detecto 13% (26 pacientes) con manifestaciones clínicas de ansiedad. La edad promedio fue 46.4 años DE ? 12.18; 58% sexo femenino y 42% sexo masculino. El estado físico fue 6% ASA I, 61% ASA II, y 33% ASA III. Las principales comorbilidades fueron: 20% enfermedad hipertensiva y 11% diabetes mellitus. Los Servicios Quirúrgicos con mayor frecuencia de ansiedad fueron: 35% traumatología y ortopedia, 16% ginecología y obstetricia, 13% cirugía general. Conclusiones: En el Hospital General Regional Núm. 1 la prevalencia de ansiedad preoperatoria es alta, La escala APAIS y Hamilton deben ser incluidas en la visita preanestésica con el objetivo de identificar a pacientes en riesgo.
Facultad de Ciencias Médicas y Biológicas. Instituto Mexicano del Seguro Social. Especialidad en Anestesiología
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16386; info:eu-repo/classification/cti/3; FCMB-E-2023-0570; Ansiedad preoperatoria; Estrés quirúrgico; Escala Hamilton